Mind Mapping sebagai Model Pembelajaran IPS Kelas V SD Muhammadiyah 16 Materi Peristiwa Detik-Detik Proklamasi - Ahsinunnikmah Ahsinunnikmah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
Social Studies which contains many memorizing material, specially about events toward Indonesian Proclamation, makes learning outcome in 5th grade SD Muhammadiyah 16 Semarang low. Teacher need to search learning model that match with Social Studies characteristic. Mind mapping model was considered can apply and increase learning outcome social studies. Method in this research using experiment. Researcher teachs students twice, with conventional model and with mind mapping model. Then compare the learning outcome. The result of this research is show that mind mapping model can increase social studies learning outcome in 5th grade SD Muhammadiyah 16 Semarang.